Respuesta :

Simplifying
2x + -5 = 4x + -1

Reorder the terms:
-5 + 2x = 4x + -1

Reorder the terms:
-5 + 2x = -1 + 4x

Solving
-5 + 2x = -1 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-5 + 2x + -4x = -1 + 4x + -4x

Combine like terms: 2x + -4x = -2x
-5 + -2x = -1 + 4x + -4x

Combine like terms: 4x + -4x = 0
-5 + -2x = -1 + 0
-5 + -2x = -1

Add '5' to each side of the equation.
-5 + 5 + -2x = -1 + 5

Combine like terms: -5 + 5 = 0
0 + -2x = -1 + 5
-2x = -1 + 5

Combine like terms: -1 + 5 = 4
-2x = 4

Divide each side by '-2'.
x = -2

Simplifying
x = -2